Missionaries of Science: The Rockefeller Foundation and Latin America, Marcos Cueto (ed.), Indiana University Press, 1994, Bloomington and Indianapolis, 171 - Myers, Jorge (1995)
Fil: Myers, Jorge. Universidad de Buenos Aires. Facultad de Filosofía y Letras.; Argentina.